Exploring the Mindset of Wonosari Village Citizens in the Mantra of the Grebeg Memetri Tradition, Tutur District, Pasuruan District (Ethnosemiotic Study) - Mardiana, Ninik; Andharu, Devito; Fadillah, M Reza Ishadi; Setyawan, Dedi (Journal Corner of Education, Linguistics, and Literature, 2024)
In the Pasuruan Regency of East Java Province, specifically in the Tutur Subdistrict, there is a village called Wonosari that holds a unique traditional ceremony to honor God, seek His blessings, and request safety from disasters for the village. The villagers of Wonosari conduct this traditional ceremony, which involves oral literature in the form of mantras. The mantras used in this tradition serve as prayers and are recited during the ritual burial of a cow's head in the center of the market. The mantras are recited by the village elders or traditional shamans during the ceremony. During the execution, the mantras are chanted aloud and listened to by the villagers of Wonosari in a solemn atmosphere.The traditional ritual of burying a cow's head in the village of Wonosari is known as Grebeg Memetri. The term "Grebeg" originates from a royal tradition aimed at distributing agricultural produce as charity to the people. The existence of mantras in the Grebeg Memetri tradition reflects the mindset of the village residents. This mindset is closely related to matters of belief, mythology, and experience. The villagers' mindset can be discerned from the oral traditions recited by the traditional shamans during the Grebeg Memetri ceremony. Investigating the mindset of the residents of Wonosari is intriguing, considering various aspects such as belief, mythology, and experience that accompany it.Given the issues described above, this research aims to examine the mindset of the residents of Wonosari through the oral tradition of Grebeg Memetri. To investigate the mindset of the villagers as manifested in the oral tradition of Grebeg Memetri, a literary approach called ethno-semiotics is required. Ethno-semiotics is an interdisciplinary field that combines ethnography and semiotics. The use of the ethno-semiotic approach is expected to represent the mindset of the residents of Wonosari based on the sign systems found in the oral tradition of Grebeg Memetri.